Pemaknaan Tata Busana Persembahyangan Untuk Meningkatkan Pemahaman Nilai Etika Dalam Ajaran Hindu (Studi Kasus Masyarakat Hindu di DKI Jakarta) - Ni Putu Alit Artiasa (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2023)
This study examines the Meaning of worshiping clothes to Increase Understanding of Ethical Values in Hinduism (A Case Study of Hindu Society in DKI Jakarta). The worship phenomenon worn by Hindu society in general, and teenagers in particular turned out to cause some problems from the point of view of Hindu ethics. This study aims to determine the meaning problem related to the changes and shifts in ethical values and clothes aesthetics of prayer based on the Balinese customs inherited in the urban environment in DKI Jakarta. The method applied in this research is qualitative method. The theoretical frameworks used as the basis for data analysis are ethical theory mainly related to ethical education, aesthetic theory, and theory of symbol related to the symbolic meaning of the temple worshiping clothes to the temple. Based on data analysis, it can be concluded: (1) change and shift of ethical value of worshiping clothes to temple for teenagers in DKI Jakarta influenced by some dominant factors, among others: the development of popular mode, multiethnic urban culture, and just follow the trend, 2) the waning of the prayer-dress ethic education is related to Balinese customs, and (3) in spite of the change, but its essential meaning is still maintained because ethics values (aesthetics and propriety) and aesthetics (harmony, beauty) are still taught in the family environment and pasraman education at the tempels.